Marine Invertebrate Peptides: Antimicrobial Peptides - Wu, Ran; Patocka, Jiri; Nepovimova, Eugenie; Oleksak, Patrik; Valis, Martin; Wu, Wenda; Kuca, Kamil (Frontiers in Microbiology, 2021)
Antimicrobial peptides are an important component of many organisms’ innate immune system, with a good inhibitory or killing effect against the invading pathogens. As a type of biological polypeptide with natural immune activities, antimicrobial peptides have a broad spectrum of antibacterial, antiviral, and antitumor activities. Nevertheless, these peptides cause no harm to the organisms themselves. Compared with traditional antibiotics, antimicrobial peptides have the advantage of not producing drug resistance and have a unique antibacterial mechanism, which has attracted widespread attention. In this study, marine invertebrates were classified into arthropods, annelids, mollusks, cnidarians, and tunicata. We then analyzed the types, sources and antimicrobial activities of the antimicrobial peptides in each group. We also reviewed the immune mechanism from three aspects: membrane-targeted direct killing effects, non-membrane targeting effects and immunomodulatory effects. Finally, we discussed their applications and the existing problems facing antimicrobial peptides in actual production. The results are expected to provide theoretical support for future research and applications of antimicrobial peptides in marine invertebrates.